2014
DOI: 10.1080/10402004.2014.933934
|View full text |Cite
|
Sign up to set email alerts
|

Tribofilm Formation and Run-In Behavior in Ultra-Low-Wearing Polytetrafluoroethylene (PTFE) and Alumina Nanocomposites

Abstract: Polytetrafluoroethylene (PTFE) and alumina nanocomposites have been of great interest to the tribological community due to the significant reduction in wear imparted by filling PTFE with low weight percentages of alumina nanofillers. The mechanisms of these three order, four order, and sometimes five order of magnitude reductions in wear have been commonly explored through evaluation of a transfer film. The present article evaluates the tribofilm formed on the wear surface of the polymer. PTFE composites with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 37 publications
(30 reference statements)
12
61
0
Order By: Relevance
“…They found that running film hardness and modulus increase with increased sliding distance and decreased wear rates [24]. They suggested that changes in mechanical properties reflect filler accumulation and tribochemical degradation of PTFE, which is consistent with their more recent papers on the evolution of interface chemistry [27,29] and particle enrichment [30].…”
Section: Mechanical Properties Of the Transfer Filmsupporting
confidence: 73%
See 3 more Smart Citations
“…They found that running film hardness and modulus increase with increased sliding distance and decreased wear rates [24]. They suggested that changes in mechanical properties reflect filler accumulation and tribochemical degradation of PTFE, which is consistent with their more recent papers on the evolution of interface chemistry [27,29] and particle enrichment [30].…”
Section: Mechanical Properties Of the Transfer Filmsupporting
confidence: 73%
“…The transfer films had the same mechanical properties as the bulk composite during the run-in, but hardness and modulus both increased significantly following the transition to ultra-low-wear sliding, as shown in Figure 7a,b. Both figures share the same trend as the mechanical evolution of running films reported by Krick et al [24]. Furthermore, there were strong correlations between transfer film mechanical properties and the system wear rater (Figure 7c,d), although the causal relationship remains uncertain; improved transfer film cohesive strength may simply be the consequence of the friction-induced polymer degradation and the accumulation of filler at the sliding interface [27,29,42].…”
Section: Mechanical Properties Of the Transfer Filmsupporting
confidence: 64%
See 2 more Smart Citations
“…There were early indications that chemistry played a role based on the observation that these ultra-low wear surfaces always exhibited a brown discoloration after transitioning to low wear [16][17] . Based on this observation alone, it is impossible to determine whether chemistry was the cause or consequence of low wear.…”
Section: Introductionmentioning
confidence: 98%